Five years of EMA-approved systemic cancer therapies for solid tumours—a comparison of two thresholds for meaningful clinical benefit. (September 2017) - Grössmann, N.; Del Paggio, J.C.; Wolf, S.; Sullivan, R.; Booth, C.M.; Rosian, K.; Emprechtinger, R.; Wild, C.
Abstract: Objective: Several societies have proposed frameworks to evaluate the benefit of oncology drugs; one prominent tool is the European Society for Medical Oncology Magnitude of Clinical Benefit Scale (ESMO-MCBS). Our objectives were to investigate the extent of European Medicines Agency (EMA)-approved cancer drugs that meet the threshold for 'meaningful clinical benefit' (MCB), defined by the framework, and determine the change in the distribution of grades when an adapted version that addresses the scale's limitations is applied. Methods: We identified cancer drugs approved by the EMA (2011–2016). We previously proposed adaptations to the ESMO-MCBS addressing its main limitations, including the use of the lower limit of the 95% confidence interval in assessing the hazard ratio. To assess the MCB, both the original and adapted ESMO-MCBS were applied to the respective approval studies. Results: In total, we identified 70 approval studies for 38 solid cancer drugs. 21% of therapies met the MCB threshold by the original ESMO-MCBS criteria. In contrast, only 11% of therapies met the threshold for MCB when the adapted ESMO-MCBS was applied. Thus 89% and 79% of therapies did not meet the MCB threshold in the adapted and original ESMO-MCBS, respectively. Conclusions: In most of the cancer drugs, the MCB threshold is not met at the time of approval when measured using both ESMO-MCBS scales. Since approval status does not translate into a MCB, stakeholders and decision makers should focus on the benefit/risk ratio of anticancer drugs to assure an appropriate allocation of resources in health care systems. Highlights: Assessment of the 'meaningful clinical benefit' of European Medicines Agency (EMA)-approved cancer drugs. Approval status does not translate into a meaningful health benefit. Contrast the limitations of the original European Society for Medical Oncology Magnitude of Clinical Benefit Scale (ESMO-MCBS). Provide an adapted value framework of the ESMO-MCBS.